Imide‐functionalized naphthodithiophene based donor‐acceptor conjugated polymers for solar cells. Issue 18 (22nd June 2013) - Dutta, Tanmoy; Li, Yong; Thornton, Aaron L.; Zhu, Da‐Ming; Peng, Zhonghua
ABSTRACT Donor‐acceptor conjugated polymers containing a new imide‐functionalized naphthodithiophene (INDT) as the acceptor unit and a 2, 2'‐bithiophene with varied substituents as the donor unit have been synthesized. The bandgaps of these polymers depend strongly on the dihedral angle of the 2, 2'‐bithiophene unit. The 3, 3'‐dialkoxy substitution (polymers PDOR/PBOR) leads to near planar bithiophene conformation due to the well‐known S–O short contact, while the 3, 3'‐dialkyl substitution (polymer PDR) results in significant twisting due to the steric effect. Consequently PDOR/PBOR shows the lowest bandgap of 1.82/1.85 eV while PDR has a bandgap of 2.38 eV. Bulk‐heterojunction solar cells of the polymer/fullerene blends have been fabricated. Preliminary results show that PBOR gives the best device performance with power conversion efficiencies as high as 2.45% in air without any thermal annealing treatment, indicating the promising potential of INDT‐containing conjugated polymers for efficient solar cells. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3818–3828